TURKISTAN GENIUS (Modern American Journal of Social Sciences and Humanities, 2025)
The article presents the work of Mahmudkhoj Behbudi, a scholar who fought for the freedom of Turkestan in the first two decades of the 20th century, the founder and leader of the Jadid movement, in the field of enlightenment, his political views, his role in the declaration of Turkestan's autonomy, and the good deeds he did to appease the people after the Bolsheviks seized power, based on concrete facts.